Incidence of Depression and Associated Factors in Patients With Type 2 Diabetes in Quebec, Canada: A Population-Based Cohort Study. Issue 21 (May 2016) - Lunghi, Carlotta; Moisan, Jocelyne; Grégoire, Jean-Pierre; Guénette, Line
Abstract : Abstract: It has been reported that the risk of depression is higher among people with type 2 diabetes compared with a nondiabetic population. Among diabetic patients, depression has been associated with worse self-care behaviors, poor glycemic control, and an increased risk of diabetes complications. Identifying factors associated with the occurrence of depression may help physicians identify earlier diabetic patients at a high risk of developing depression, improve prevention, and accelerate proper treatment. To our knowledge, very few population-based studies have reported on the incidence of clinically diagnosed depression as a consequence of type 2 diabetes over a long follow-up period. The objective of this study was to estimate the incidence of clinically diagnosed depression among type 2 diabetic patients newly treated with oral antidiabetic drugs (ADs) and to identify factors associated with the occurrence of depression. Administrative claims data from the public health insurance plan were used to identify a cohort of new oral AD users aged ≥18 years between 2000 and 2006. Patients were followed from oral AD treatment initiation until the diagnosis of depression, ineligibility for the public drug plan, death, or the end of the study, whichever came first. Incidence rates were determined using person-time analysis. Factors associated with depression were identified using multivariable Cox regression analysis. We identified 114, 366 new oral AD users, of which 4808 had a diagnosis of depression. The overall incidence rate of depression was 9.47/1000 person-years (PYs) (10.72/1000 PYs for women and 8.27/1000 PYs for men). The incidence of depression was higher during the year after oral AD treatment initiation. Independent factors associated with depression included having had mental disorders other than depression, hospitalization, a higher number of different drugs taken and of physicians visited during the year before oral AD initiation. Moreover, we observed a statistically significant age-by-socioeconomic status interaction. The incidence of diagnosed depression is higher during the first year after oral AD treatment initiation. Clinicians could pay particular attention to women, patients starting an AD at a young age, those with a low socioeconomic status, and especially those with a history of anxiety or dementia. Abstract : Supplemental Digital Content is available in the text